The functional composition of the benthic invertebrate community of the Mondego estuary : insights within the functioning of this ecosystem - Linden, Pieter van der (2011)
Dissertação de mestrado em Ecologia, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra